147 Body mass index-associated differences in cardiac stress energetics in type 2 diabetes. (6th June 2022) - Chowdhary, Amrit; Cubbon, Richard; Thirunavukarasu, Sharmaine; Jex, Nicholas; Kotha, Sindhoora; Xue, Hui; Kellman, Peter; Greenwood, John P; Plein, Sven; Levelt, Eylem
Abstract : Background: The incidence of type 2 diabetes (T2D) continues to increase, driven predominantly by the obesity epidemic. Many patients with T2D and heart disease have normal body mass index (BMI), suggesting that diabetes and obesity mediate cardiovascular change by different mechanisms, and that diabetic cardiomyopathy may occur in patients with T2D without obesity. We have previously demonstrated that irrespective of BMI, diabetes is related to significant abnormalities in cardiac structure and rest energetics, and to cardiac steatosis. However, changes in cardiac energy metabolism in lean diabetic patients during exercise stress have not been previously reported.ObjectivesWe aimed to assess if there are BMI-associated differences in cardiac stress metabolism in patients with T2D. Methods Twenty-five overweight T2D patients (O-T2D) (17 male, mean age 60±8 years; BMI 31±4kg/m2; mean HbA1c of 59±12 mmol/mol) and eleven lean T2D patients (LnT2D) (6 male, mean age 56±9 years; BMI 23±1kg/m2, mean HbA1c of 59±14 mmol/mol), age- and ethnicity-matched and with no other comorbidities were studied. Patients were on oral hypoglycaemics only and were free of diabetes complications. Participants underwent rest and dobutamine stress phosphorus magnetic resonance spectroscopy (31P-MRS) and cardiovascular magnetic resonance (CMR) at 3T for the assessment of myocardial phosphocreatine to ATP ratio (PCr/ATP) as a measure of myocardial energetics, biventricular volumes, rest and stress left ventricular (LV) ejection fraction, global longitudinal shortening, and mitral in-flow E/A ratio for assessment of diastolic function and perfusion. Intravenous Dobutamine was administered at a dose of 5 μg/kg/min, increasing at 90 second intervals up to a maximum of 40 μg/kg/min to achieve a target heart rate of 65% of the age-predicted maximal heart rate. Participants had continuous ECG monitoring and regular non-invasive blood pressure monitoring. Mean rate pressure product (RPP) was recorded at rest and stress. Heart rate was maintained at target for the duration of the 31P-MRS and stress CMR cine, mitral in-flow and perfusion acquisitions. Results: The cardiac volumes, systolic or diastolic function and LV mass were similar between LnT2D and O-T2D. Although the O-T2D patients had a numerically lower rest and stress PCr/ATP ratio, this did not reach statistical significance. Resting PCr/ATP was reduced in LnT2D and O-T2D patients similarly. However, LnT2D showed a greater reduction in PCr/ATP (stress PCr/ATP LnT2D 1.51± 0.2 vs O-T2D 1.41±0.25, p=0.02) despite similar increases in RPP. Stress myocardial blood flow (MBF) was also significantly lower in the O-T2D patients. There were significant correlations of BMI with LV mass (r=0.35, p=0.03); stress LVEF (r=-0.34, p=0.04); stress MBF stress (r=-0.53, p=0.001) and stress E/A (r=0.46, p=0.01) (figure 1). Conclusions: Despite their better stress perfusion and similar glycaemic control, lean patients with T2D show worse metabolic reserve characterised by more more significant decrements in energetics in response to hemodynamic stress compared to overweight patients with T2D. Higher BMI correlates inversely with stress myocardial blood flow and with stress left ventricular ejection fraction. The presence of these subtle alterations in measures of stress metabolism and perfusion might signify a distinct metabolic phenotype of 'lean diabetic cardiomyopathy'. Future studies are needed to further delineate alterations in cardiac energy metabolism in lean and overweight/obese type 2 diabetes patients, and their role in the development of cardiac dysfunction. Conflict of Interest: Nil